Pengaruh Kepemimpinan Dan Motivasi Belajar Terhadap Lulusan Siswa SMK Sadar Wisata Ruteng-Nusa Tenggara Timur - Leonardus W.Dino Setiawan; Petrus Herson Hadun (Jurnal Manajemen, 2019)
Background.The teacher's role as a leader and motivator in theteaching and learning process can stimulate students to increasetheir competency according to the K-13 curriculum. The mastery ofcompetencies in each subject is measured by the graduation ofstudents at final exam. The graduation accumulation is reflected inthe graduation presentation of each educational institution. Purpose.The study analyzed the effect of leadership and learning motivationon increasing student graduation at High School of Sadar Wisata in2018/2019. Method. Using survey-cross sectional method. Theresearch population of graduates in 2018/2019 was 256 people. Thesample of 60 people with purporsif sampling technique. Duration ofstudy: During June-July 2019. Research location, High School ofSadar Wisata Ruteng. Results. Leadership has a significant effect onthe percentage of student graduation (Î± = 0.002; <0.05), alsomotivation to learn has a significant effect (Î±=0.00; <0.05) on thepercentage of student graduation. If the dominance of the influenceof the two independent variables is examined, it is found that thevariable of learning motivation (Î² = .441) is more dominant than theleadership variable (Î² = .388). Conclusion. Teachers as leaders andmotivators are needed by students in the learning process. As aleader a teacher guides students to follow the learning processcarefully, as motivator the teacher moves students to carry outactivities in the learning process to accumulate on the achievement ofstudent competencies. Competency mastery is indicated throughstudents' graduation at final examination.